2019
DOI: 10.1007/s12274-019-2308-9
|View full text |Cite
|
Sign up to set email alerts
|

Chemotherapy drugs derived nanoparticles encapsulating mRNA encoding tumor suppressor proteins to treat triple-negative breast cancer

Abstract: Triple-negative breast cancer (TNBC) is one type of the most aggressive breast cancers with poor prognosis. It is of great urgency to develop new therapeutics for treating TNBC. Based on current treatment guideline and genetic information of TNBC, a combinational therapy platform integrating chemotherapy drugs and mRNA encoding tumor suppressor proteins may become an efficacious strategy. In this study, we developed paclitaxel amino lipid (PAL) derived nanoparticles (NPs) to incorporate both chemotherapy drugs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
39
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 41 publications
(42 citation statements)
references
References 53 publications
0
39
0
Order By: Relevance
“…[ 26 ] The EPR effect has been a longstanding paradigm in cancer nanomedicine, and has been exploited as the main tumor delivery mechanism for different types of nanoparticles, including inorganic (such as noble metal, oxide, upconversion, and carbon‐based nanoparticles) and organic nanoparticles (such as liposomes or lipid‐based nanoparticles, polymeric nanoparticles and dendrimers). [ 25,46–53 ] However, it is not the only pathway for nanoparticles to cross tumor blood vessels, as depicted in Figure . In general, we can differentiate two main nanoparticle transport pathways: i) paracellular transport by diffusion through intercellular gaps; and ii) transcellular nanoparticle transport through tumor endothelial cells.…”
Section: The Tumor Microenvironment and Vasculaturementioning
confidence: 99%
“…[ 26 ] The EPR effect has been a longstanding paradigm in cancer nanomedicine, and has been exploited as the main tumor delivery mechanism for different types of nanoparticles, including inorganic (such as noble metal, oxide, upconversion, and carbon‐based nanoparticles) and organic nanoparticles (such as liposomes or lipid‐based nanoparticles, polymeric nanoparticles and dendrimers). [ 25,46–53 ] However, it is not the only pathway for nanoparticles to cross tumor blood vessels, as depicted in Figure . In general, we can differentiate two main nanoparticle transport pathways: i) paracellular transport by diffusion through intercellular gaps; and ii) transcellular nanoparticle transport through tumor endothelial cells.…”
Section: The Tumor Microenvironment and Vasculaturementioning
confidence: 99%
“…Compound 1, vitamin B3 derivative, vitamin C derivative, vitamin D derivative, vitamin E derivative, and vitamin H (also called vitamin B7) derivative, were synthesized according to the methods reported previously 25 .…”
Section: Synthesis Of Vitamin-derived Lipidsmentioning
confidence: 99%
“…mRNAs used in this study were constructed by our mRNA platform based on the reported method 25 . The preparation of mRNA LNPs was reported previously 26 .…”
Section: Preparation Characterization and Optimization Of Vlnpmentioning
confidence: 99%
“…Cancer [ 218] LPPs triMannose-lipid/lipid 1/lipid 2 + PEG-HpK Ag (MART-1) I.D. APCs Cancer [ 133] EDOPC/DOPE/DSPE-PEG2k+PbAE Ag (OVA) I.V.…”
Section: Ly6c+ Inflammatory Leukocytesmentioning
confidence: 99%
“…[145,146,217] Restoring tumor suppressor genes can not only induce tumor cell apoptosis, but also sensitize tumor cells to chemotherapy. [218] It has been found that p53 restoration in p53-deficient HCC and NSCLC tumor cells can induce tumor cell apoptosis via PUMA-Cas9/Cas3 pathway and G1-phase cell cycle arrest via p21/CyclinE1 pathway. [219] p53 restoration can also synergize with chemotherapy drugs such as everolimus in cancer cell killing without causing severe toxicity.…”
Section: Cancer Treatmentmentioning
confidence: 99%